Design and Implementation of Mobile Native Application - Erika Ramadhani (International Journal of Computer and Information System (IJCIS), 2023)
Virtual money is very popular in Indonesia, the integration of many type of virtual money into one application enable the user to check many type of virtual money application easily into one platform according to a mobile native application. Mobile applications that have not used native technology have problems, that is, if one of the services is a system failure, the other system is experiencing problems as well. The objective of this paper is to overcome the problem, we made an application using native technology. We analyze the system according to the performance of the system by comparing when using native system and conventional application. This paper has a several steps as the method to reach the result, such as literature review, requirement analysis, design, implementation, and testing. The use of native technology does not cause system failure if one of the modules has an error. The development of a mobile native application for e-money using Native React and Firebase in the Android platform. The service of the application of e-money is enable to check the balance of the money in several type of virtual money application such as Bukalapak, Jakmall, Paypal, and several type of government bank. API service is used to integrate many platforms named Finfini.  Furthermore, this API enables the mobile e-money application to communicate with a cross platform virtual money. The results of testing, the e-monies system using native technology has a performance of 13% better in using resources when compared to conventional applications